O ENSINO INTEGRADO NO IFSUL - CAMPUS BAGÉ: UM OLHAR SOBRE A MATEMÁTICA EM DOIS CURSOS INTEGRADOS DE NÍVEL MÉDIO E CONTRIBUIÇÕES PARA A PRÁTICA DOCENTE - Sonza, Aline Picoli (2023)
The expansion of access to the federal education network and the growth of the intermediate level integrated technical teaching are indicated as important tendencies of the last few years in Brazil. The integration can be seen as a possibility of a knowledge development, which is able to give a new meaning to the process of teaching and learning. Mathematics, besides the importance of the specific concepts, becomes an instrument which enables the development of logical thinking and abstraction, besides being indispensable to the knowledge construction in other areas, such as physics and chemistry, among others. Thus, it can be seen as a curricular component that is able to navigate and dialogue more easily within the distinct knowledge areas. The objective of this present study is to discuss about the High School Integrated Technician Teaching, analyzing the way its implementation happens at IFSUL- campus in Bagé, and, furthermore, build a support didactic material to contribute to the construction of integrated proposals in the mathematics teaching in the integrated technical courses from the campus. The research methodology about the study of the case using the conceptions from Yin was the option chosen for the development of this project. The results point out that integrated teaching is not a reality on campus and, within the aspect which makes its implementation more difficult, it highlights the fact that a lot of other teachers don’t know the principles of integration and others know it superficially. Upon this observation, a didactic material as a support to the integration (DMSI) was built, with the collaboration from teachers from different technical areas of the two courses involved in the proposal. After the assessment from DMSI, performed by mathematics teachers, it can represents the perspective of turning possible discussions, reflections and studies about the integrated teaching subject, in other words, DMSI can be considered as a document which carries the expectation of the beginning of movements and transformations in direction to a teaching based on a dialogue between the areas. It is highlighted the relevance of this unprecedented research in a situation where the integrated teaching should be a frequent subject of discussion and, as well, for the fact that there is a significant deficiency in studies and researches involving the integrated teaching and mathematics in Brazil and, specially, emphasizes approaches in the teaching practice which points to integration possibilities.